Entrepreneurship; The Future Research Agendas - Mohammad Arif (Trunojoyo University of Madura, 2016)
The entrepreneurship concept has grown quickly. Starting from the behavioral approach (Miller, 1983; Covin and Slevin. 1991; Stevenson and Jarillo, 1990), process(Mintzberg, 1973; Lumpkin and Dess 1996;) and strategic approach (Venkatraman andSarasvathy, 2001). Each of these perspectives has been widely accepted and someresearchers have done the appraisal, either empirically or conceptually. One of thefactors that drive the development of the concept of entrepreneurship is the behavioralapproach as a result of business activities. The behavior is dynamic andmultidimensional. Therefore, the concept of entrepreneurship can be developed intoanother perspective. Some researchers give recommendations about theentrepreneurship development based on religiosity and genetic